ENCOURAGING LEARNING QUALITY THROUGH BLENDED LEARNING MODEL - Susilawati, Samsul; Hambali, Moh.; Yasin, Ahmad Fatah; Chakim, Abdulloh; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2020)
The development of information technology makes educational institutions have to improvise in relevant learning models in order to compete with other higher education in the world. However, it has been noted that Islamic higher education has not been able to adapt quickly in this context. This study aims to explore the use of blended learning models to improve the quality of learning at public Islamic universities in Indonesia. By collecting data from classroom learning practices directly and analyzing them descriptively qualitatively, this study found that the Blended Learning Model was implemented effectively through Website Based Learning and Edmodo Applications. In addition, this study also found that the use of both types of approaches can improve the effectiveness and quality of learning in the classroom.